Major clonal lineages in impetigo Staphylococcus aureus strains isolated in Czech and Slovak maternity hospitals - Růžičková, Vladislava; Pantůček, Roman; Petráš, Petr; Machová, Ivana; Kostýlková, Karla; Doškař, Jiří (International journal of medical microbiology, 2012)
One hundred and twenty-seven exfoliative toxin-producing (ET-positive) strains of Staphylococcus aureus collected in 23 Czech and one Slovak maternity hospitals from 1998 to 2011 were genotypically characterized by multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE) profiling, spa gene polymorphism analysis, and ETA-converting prophage carriage, which resulted in the identification of 21 genotypes grouped into 4 clonal complexes (CC). Ninety-one isolates carried the eta gene alone whilst 12 isolates harboured only the etb gene. Two new, to date not defined, spa types (t6644 and t6645) and 2 novel sequence types (ST2194 and ST2195) were identified in the set of strains under study. The predominant CC121 occurred in 13 Czech hospitals. CC15, CC9, and ST88 (CC88) exclusively included eta gene-positive strains while the strains belonging to ST121 harboured the eta and/or etb genes. This study highlights not only significant genomic diversity among impetigo strains and the distribution of major genotypes disseminated in the Czech and Slovak maternity hospitals, but also reveals their impact in epidermolytic infections.
Keywords: genotyp; techniky typizace bakterií; Genotype; Czechoslovakia; Staphylococcal Infections; Československo; Carrier State; porodnice; stafylokokové infekce; fenotyp; bakteriální geny; polymorfismus genetický; Hospitals, Maternity; Bacterial Typing Techniques; Staphylococcus aureus; Base Sequence; sekvence nukleotidů; Infant, Newborn; Multilocus Sequence Typing; Phenotype; Polymorphism, Genetic; novorozenec; Humans; Equipment and Supplies, Hospital; Genes, Bacterial; pulzní gelová elektroforéza; přenašečství; multilokusová sekvenční typizace; Electrophoresis, Gel, Pulsed-Field; Impetigo; impetigo; lidé; vybavení a zásoby nemocnice